The Opposing Effect of Type I IFN on the T Cell Response by Non-modified mRNA-Lipoplex Vaccines Is Determined by the Route of Administration - Lien Van Hoecke; Kenny Roose; Marlies Ballegeer; Zifu Zhong; Niek N. Sanders; Stefaan De Koker; Xavier Saelens; Sandra Van Lint (Elsevier, 2020)
mRNA-lipoplex vaccines are currently being explored in phase II clinical trials for the treatment of patients with advanced solid tumors. Mechanistically, these mRNA-lipoplex vaccines are characterized by the induction of type I interferon (IFN) centered innate responses. Earlier studies have identified type I IFNs as major regulators of the T cell response instigated by mRNA-lipoplex vaccines. However, stimulatory or, in contrast, profound inhibitory effects of type I IFNs were described depending on the study. In this mouse study, we demonstrated that the opposing roles of type I IFN signaling on the magnitude of the vaccine-evoked T cell responses is dependent on the route of mRNA-lipoplex administration and is regulated at the level of the T cells rather than indirectly through modulation of dendritic cell function. This study helps to understand the double-edged sword character of type I IFN induction upon mRNA-based vaccine treatment and may contribute to a more rational design of mRNA vaccination regimens.